The Correlation Between Children Who Use Bottle Feeding Ages 4 - 6 Years Against The Malocclusion - Faziha Nurul Imani; Eddy Heriyanto Habar (Makassar Dental Journal, 2020)
ABSTRACT Background: The prevalence of malocclusion in Indonesia is still very high at around 80% of the population and is one of the major dental and oral health problems, this is coupled with a low level of dental care awareness. The prevalence of malocclusion because of the habit of drinking milk with bottle feedings was 49.5% of 377 children. This is habit because, the habit of drinking milk with a bottle feeding causes the movement of the baby's tongue like a sucking motion. This abnormal tongue motor activity will result in aberrant swallowing habits which will eventually cause malocclusion. Purpose: To determine the correlation between children using bottle feeding aged 4 - 6 years to the occurrence of malocclusion. Methods: This study uses the Analytical Observational method with a cross sectional study design. The sample consisted of 30 children aged 4 - 6 years who met the criteria of the study determined by filling out questionnaires and intra-oral examination of samples Result: The result of Spearman's correlation statistical test, obtained the correlation coefficient value (r=0.435) which shows a moderate correlation. The results of the linear regression test to see if there are long-term effects of using a bottle feeding on the occurrence of malocclusion, obtained a value (p <0.05) which shows a significant effect. Conclusion: There is a moderate correlation between children who use bottle feedings aged 4-6 years to malocclusion. The longer children use bottle feeding, the more severe the malocclusion of children. Keywords: Malocclusion, Bottle feeding